2021
DOI: 10.3390/catal11111304
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Parameter Identification of a Fixed-Bed Reactor Model for Catalytic CO2 Methanation Using Physics-Informed Neural Networks

Abstract: In this study, we develop physics-informed neural networks (PINNs) to solve an isothermal fixed-bed (IFB) model for catalytic CO2 methanation. The PINN includes a feed-forward artificial neural network (FF-ANN) and physics-informed constraints, such as governing equations, boundary conditions, and reaction kinetics. The most effective PINN structure consists of 5–7 hidden layers, 256 neurons per layer, and a hyperbolic tangent (tanh) activation function. The forward PINN model solves the plug-flow reactor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…Recent advances in physics-informed learning have demonstrated their potential in dealing with inverse problems in chemical reactions, such as unknown parameter identification and reaction network discovery, which can greatly improve our understanding of complex reaction processes and lead to more accurate and reliable models. For instance, Ngo et al 34 applied inverse PINN methods to obtain the unknown parameter (effectiveness factor) of a highly nonlinear reaction rate model for catalytic CO 2 methanation in an isothermal fixed-bed reactor. The results showed that it was able to identify an unknown effectiveness factor with an error of 0.3%, even for a small number of observation datasets.…”
Section: Chemical Reactionmentioning
confidence: 99%
“…Recent advances in physics-informed learning have demonstrated their potential in dealing with inverse problems in chemical reactions, such as unknown parameter identification and reaction network discovery, which can greatly improve our understanding of complex reaction processes and lead to more accurate and reliable models. For instance, Ngo et al 34 applied inverse PINN methods to obtain the unknown parameter (effectiveness factor) of a highly nonlinear reaction rate model for catalytic CO 2 methanation in an isothermal fixed-bed reactor. The results showed that it was able to identify an unknown effectiveness factor with an error of 0.3%, even for a small number of observation datasets.…”
Section: Chemical Reactionmentioning
confidence: 99%
“…(a) PINN without transport effect, able to solve both inverse and forward kinetic problems (Gusmão et al); (b) PINN with transport effect in a fixed bed reactor for catalytic CO 2 methanation, able to solve inverse kinetic problems (Ngo and Lim). Figure 18a was adapted with permission from ref .…”
Section: Current Status and Challengesmentioning
confidence: 99%
“…Another typical example is illustrated in Figure b, where the classic reactor model is used to consider the transport effect in an isothermal fixed bed reactor for catalytic CO 2 methanation. Ngo and Lim trained an effective physics-informed feed-forward ANN. In particular, a classic plug-flow fixed bed reactor model was introduced to consider the effect of transport phenomena, and the unknown effectiveness factor existing in reaction kinetics can be estimated with a 0.3% error even for a limited number of data sets.…”
Section: Current Status and Challengesmentioning
confidence: 99%
“…However, the study on this matter in the engineering area is currently still at the stage of using ordinary DNN [25][26] and time series forecasting models such as LSTM [27]. On the other hand, all existing data-driven methods for CODES are based on PINN and therefore cannot handle parametric CODES [6,28,29]. Following the concept of PINO, we aim to propose a physicsinformed neural operator PINO-MBD for CODES in MBD.…”
Section: Machine Learning-based Pde Solversmentioning
confidence: 99%